Mechanisms of hypnosis: toward the development of a biopsychosocial model - Jensen, Mark P.; Adachi, Tomonori; Tomé Pires, Catarina; Lee, Jikwan; Jamil @ Osman, Zubaidah; Miró, Jordi (Routledge, 2015)
Evidence supports the efficacy of hypnotic treatments, but there remain many unresolved questions regarding how hypnosis produces its beneficial effects. Most theoretical models focus more or less on biological, psychological, and social factors. This scoping review summarizes the empirical findings regarding the associations between specific factors in each of these domains and response to hypnosis. The findings indicate that (a) no single factor appears primary, (b) different factors may contribute more or less to outcomes in different subsets of individuals or for different conditions, and (c) comprehensive models of hypnosis that incorporate factors from all 3 domains may ultimately prove to be more useful than more restrictive models that focus on just 1 or a very few factors.